Easy in, Easy out: Are Alternatively Certified Teachers Turning Over at Increased Rates?. (August 2016) - Redding, Christopher; Smith, Thomas M.
Alternative certification programs are now commonplace in the credentialing of new teachers. We complement the growing evidence base for these teachers by exploring their turnover patterns in four waves of the nationally representative Schools and Staffing Survey (SASS). We report on descriptive evidence of growing differences in the characteristics of alternatively and traditionally certified teachers and the schools in which they teach. Controlling for factors that predict higher turnover, we find that by the 2007–2008 school year, alternatively certified teachers were still more likely than traditionally certified teachers to leave the profession. We find some evidence that an increase in the number of organizational supports for new teachers may reduce the likelihood of turnover.